The role of Pnut and its functional domains in Drosophila spermatogenesis - K. A. Akhmetova; N. D. Dorogova; E. U. Bolobolova; I. N. Chesnokov; S. A. Fedorova (Вавиловский журнал генетики и селекции)
Drosophila Pnut protein belongs to the family of septins, conservative GTPases participating in cytokinesis and many more other fundamental cellular processes. Because of their filamentous appearance, membrane association and functions, septins are considered as the fourth component of the cytoskeleton, along with actin, microtubules and intermediate filaments. However, septins are much less studied than the other cytoskeleton elements. We had previously demonstrated that deletion of the peanut (pnut) gene leads to mitotic abnormalities in somatic cells. The goal of this work was to study the role of pnut in Drosophila spermatogenesis. We designed a construct for pnut RNA interference allowing pnut expression to be suppressed ectopically. We analyzed the effect of pnut RNA interference on Drosophila spermatogenesis. The most sensitive to Pnut depletion were germ line cells at the earliest stages of spermatogenesis: the suppression of pnut expression at these stages leads to male sterility as a result of immotile sperm. Testes of those sterile males did not show any significant meiotic defects; axonemes and mitochondria were normal. We also analyzed the effect of mutations in Pnut conservative domains on Drosophila spermatogenesis. Mutations in the GTPase domain resulted in cyst elongation defects. Deletions of the C-terminal domain led to abnormal testis morphology. Both GTPase domain and C-terminal domain mutant males were sterile and produced immotile sperm. To summarize, we showed that Pnut participates in spermiogenesis, that is, late stages of spermatogenesis, when major morphological changes in spermatocytes occur.